Regulations Shape Transparency, Accountability, and Managerial Traits in School Funds - Ratih Kumara Dewi; Nur Fadjrih Asyik; Lilis Ardini (Journal of Accounting Science, 2026)
General Background: The management of School Operational Assistance (BOS) funds by the government is an important element in maintaining the stability and quality of educational services in private vocational schools. Specific Background: The effectiveness of its management is often hampered by weak integration between managerial factors and compliance with applicable regulations. Knowledge gap: Previous studies tend to analyse the variables of transparency, accountability, and managerial characteristics separately, and there is still a gap in exploring the role of regulation as an interactive factor that moderates these relationships. Objective: This study aims to analyse the influence of transparency, accountability, and managerial characteristics on the effectiveness of BOS funds and to evaluate the moderating role of regulations. Method: This quantitative study uses a survey method on 83 respondents in Sidoarjo, which is analysed using an inferential statistical approach. Results: Transparency and regulations have a significant positive influence on the effectiveness of BOS fund management, while accountability and managerial characteristics have no influence. Regulations are proven to strengthen the relationship between transparency and management effectiveness. Novelty: Unlike previous studies that placed regulation as a driving variable, this study introduces regulation as a quasi-moderator that has a weakening effect on the relationship between transparency and the effectiveness of BOS fund management. Implications: These findings indicate that the effectiveness of BOS fund management cannot be achieved solely through quantitative strengthening of regulations, but rather requires simplification of rules to ensure that transparency remains the primary driver of performance without being hindered by administrative burdens.